Iterative Model Reconstruction (IMR) in MDCT Below 2 mSv for the Detection of Urinary Calculi: Diagnostic Accuracy and Image Quality in Comparison to Filtered Back-Projection and 4th Generation Iterative Reconstruction (iDose4) - Schmidt-Holtz, Jakob; Laqmani, Azien; Butscheidt, Sebastian; Kurfürst, Max; Avanesov, Maxim; Behzadi, Cyrus; Spink, Clemens; Veldhoen, Simon; Nagel, Hans Dieter; Adam, Gerhard; Regier, Marc (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose The purpose of the study was to assess the impact of iterative model reconstruction (IMR) on reader confidence with respect to stone detection and image quality in comparison to filtered back-projection (FBP) and iDose level 4 (iDose4) in abdominal MDCT with radiation doses below 2 mSv.Materials and Methods For 32 consecutive patients with suspected ureteral stone disease, the raw data of unenhanced 256 slice MDCT (120 kV, 40 reference mAs, mean CTDIvol: 2.7 ± 0.8 mGy, mean DLP: 126 ± 38 mGy × cm) were reconstructed using a prototype version of IMR (levels 1 – 3), iDose4 (level 4) and FBP at a 3 mm slice thickness. Image analysis was independently performed by two radiologists in a blinded fashion. The reader confidence level with respect to stone detection was recorded based on a 5-point scale (1 – certain exclusion; 5 – concrement definitely present) as well as for the evaluation of image quality regarding the depiction of anatomical details (1 – poor; 5 – excellent). A clinical reference standard for stone detection was not established. Statistical evaluation included weighted kappa analysis and Wilcoxon test.Results 17 pelvic and ureteral stones were found. 11 further concrements were located within the ostium of the urinary bladder or the bladder itself. Applying IMR, a distinct improvement in image quality was observed at every level (mean value for FBP, 2.0; iDose4, 2.9; IMR L1, 4.2; IMR L2, 4.0; IMR L3, 3.9; all p < 0.001). Applying the higher IMR levels L2 and L3, a certain level of so-called “blotchiness” of anatomical contours was observed. Reader confidence was significantly improved and was independent of IMR level (certain stone detection FBP, 69 %; iDose4, 81 %; IMR L1 to L3, 95 %; all p > 0.001). With increasing IMR levels, the reduction in streak artifacts was quantified by a decrease in image noise. A loss of anatomical information was not observed. The sensitivity rates for stone detection were equivalent for all MDCTs reconstructed with FBP, iDose4 and IMR. A mean effective dose of 1.9 ± 0.6 mSv was calculated.Conclusion In comparison to FBP and iDose4, a significant increase in mean image quality, reduction in image noise and improvement in subjective reader confidence can be achieved by applying IMR even at significantly reduced dose settings below 2 mSv. Results indicate that a further dose reduction might be possible with IMR.Key Points Citation Format
Keywords: abdomen; image manipulation/reconstruction; CT; ureter; urinary tract; urolithiasis